2021
DOI: 10.3390/vaccines9121458
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination in People Living with HIV (PLWH) in China: A Cross Sectional Study of Vaccine Hesitancy, Safety, and Immunogenicity

Abstract: The administration of COVID-19 vaccines is the primary strategy used to prevent further infections by COVID-19, especially in people living with HIV (PLWH), who are at increased risk for severe symptoms and mortality. However, the vaccine hesitancy, safety, and immunogenicity of COVID-19 vaccines among PLWH have not been fully characterized. We estimated vaccine hesitancy and status of COVID-19 vaccination in Chinese PLWH, explored the safety and impact on antiviral therapy (ART) efficacy and compared the immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
47
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 36 publications
9
47
1
1
Order By: Relevance
“…Contrary to the findings of Liu, 22 who reported that PLWH have spike receptor binding domain-protein specific IgG (S-RBD-IgG) antibody titers comparable to those of healthy controls following inactivated COVID-19 vaccination, our study revealed a poor immune response in PLWH compared with HDs. This discrepancy may be due to differences in detection indicators.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the findings of Liu, 22 who reported that PLWH have spike receptor binding domain-protein specific IgG (S-RBD-IgG) antibody titers comparable to those of healthy controls following inactivated COVID-19 vaccination, our study revealed a poor immune response in PLWH compared with HDs. This discrepancy may be due to differences in detection indicators.…”
Section: Discussioncontrasting
confidence: 99%
“… 21 Further analysis revealed a markedly lower antibody level in patients with CD4 + T-cell counts ≤350 cells per μL, consistent with the finding that CD4 + T-cell count is positively correlated with neutralizing antibody responses to inactivated SARS-CoV-2. 22 , 23 Therefore, a booster dose or dose adjustment might be needed in HIV-infected individuals, especially those with lower CD4 + T-cell counts.…”
Section: Discussionmentioning
confidence: 99%
“…Our results on the humoral immune response are in agreement with other reports that reported on immunogenicity and safety of COVID-19 vaccines 55, 56, 57 . In contrast, similar antibody responses were reported in a PLWH cohort that received an inactivated SARS-CoV-2 vaccine 58 .…”
Section: Discussionsupporting
confidence: 73%
“…Our study contributes to the limited literature on vaccine hesitancy among the nationwide sample of PWH living in the U.S., revealing most participants having some levels of hesitancy concerning COVID-19 vaccination. Previously reported vaccine hesitancy rates range from 22% to 42.4% among the adult American population [ 5 , 6 , 7 , 31 ] and 27.5% to 38.4% among PWH across various settings [ 32 , 33 , 34 ]. It is troubling that the vaccine hesitancy among PWH in our sample fell on the higher side of these ranges, as the pandemic adversely impacts HIV care with increasing loss to follow-up or disengagement [ 8 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These included concerns about the efficacy, safety, and side effects of the vaccine. Although COVID-19 vaccine hesitancy among PWH across the globe is still advancing, multiple studies have already highlighted similar findings across various settings [ 32 , 33 , 34 ]. This finding becomes especially relevant in the context of the reported mistrust in COVID-19 or COVID-19 vaccine information sources, which has also been correlated with vaccine hesitancy [ 8 , 32 ].…”
Section: Discussionmentioning
confidence: 99%